Health system preparedness for newborn care: a health facility assessment in rural Uganda - Kayemba, Christine; Peterson, Stefan; Tomson, Goran; Guwatudde, David; Kiguli, Juliet; Namazzibner Tagoola4, Gertrude Peter Waiswa1,2; Namutamba, Sarah; Namugaya, Faith; Nambuya, Harriet (BMC Health Services Research, 2014)
Newborn deaths must be reduced to achieve Millennium Development Goal four. Health facilities have a critical role to play in the fight to save the 2.9 million newborns that die in the world every year. It is not clear if health facilities in rural Uganda have the capacity to care for newborns. To assess the capacity of health facilities to care for newborns in Iganga and Mayuge districts in eastern Uganda for the three main mortality causes: preterm/ low birth weight, asphyxia and sepsis.
Keywords: Health system preparedness; Newborn care; Health facility; Rural Uganda